2009
DOI: 10.1007/s12560-009-9010-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Study of the Persistence of Infectious Human Norovirus on Food-Contact Surfaces

Abstract: The aim of this study was to investigate the effect of relative humidity (RH) and temperature on norovirus (NoV) persistence as infectious particles on food-contact surfaces such as stainless steel and polyvinyl chloride (PVC). For this purpose, a new method combining enzymatic digestion with molecular beacon-based NASBA targeting the ORF1-ORF2 domain was developed to discriminate between infectious and noninfectious NoV. Stainless steel and PVC disks were contaminated with known amounts of human NoV and kept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…One of the critical factors of HuNoV transmission is its ability to persist long term in the environment. Lamhoujeb et al (2009) reported that HuNoVs can persist on stainless steel and polyvinylchloride (PVC) surfaces for from 1 to more than 7 weeks, depending on the surface, temperature, and relative humidity (24). In addition, once a surface becomes contaminated, virus particles can easily be transferred between inanimate and animate objects (e.g., from contaminated surfaces to hands and vice versa) (3,20).…”
mentioning
confidence: 99%
“…One of the critical factors of HuNoV transmission is its ability to persist long term in the environment. Lamhoujeb et al (2009) reported that HuNoVs can persist on stainless steel and polyvinylchloride (PVC) surfaces for from 1 to more than 7 weeks, depending on the surface, temperature, and relative humidity (24). In addition, once a surface becomes contaminated, virus particles can easily be transferred between inanimate and animate objects (e.g., from contaminated surfaces to hands and vice versa) (3,20).…”
mentioning
confidence: 99%
“…It has been implied that electrostatic forces play a major role in controlling virus adsorption to lettuce (Lamhoujeb et al 2009). Many theories for the outbreaks associated with lettuce exist, including that lettuce seems to have the highest adsorption capacity and the most favorable conditions for viral 95 bp → 155 bp → ← 95 bp ← 155 bp (b) (a) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 persistence because of the size and the wrinkled texture of its leaves (Croci et al 2002), compared to other smooth, flat surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Readers interested in additional information on this topic are referred to certain of the references [8,9,10,12,18,19,20,22,30,31]. …”
Section: Resultsmentioning
confidence: 99%